The interference of the use of technologies (social media and games) in the quality of sleep and teaching process learning of High School students: systematic review (Research, Society and Development, 2022)
This review sought to carry out a synthesis of the literature regarding the impacts of the use of technologies on sleep quality and on the learning process of high school students. A systematic literature review was carried out according to the Prisma protocol (Preferred Reporting Items for Systematic Reviews and Which we used the PubMed, SciELO and Web of Science databases, including published observational studies published between the years 2014 and 2020, that assess the interference of the use of equipment on sleep quality and, consequently, do not meet the performance. There was no language limitation in the search. A total of 153 studies were found with the electronic search. Of these, only 4 met the inclusion criteria Multiple studies are electronic factors that the use of social equipment, or entertainment through access to games, has had an impact on the lives of adolescents. social media, has interfered with sleep quality, being one of the factors associated with a reduction in school performance of teaching students.